2007
DOI: 10.1002/jcop.20165
|View full text |Cite
|
Sign up to set email alerts
|

Community social and place predictors of sense of community: A multilevel and longitudinal analysis

Abstract: Ⅲ Sense of community (SOC) is empirically "unpacked" as a multilevel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
88
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 39 publications
0
88
0
5
Order By: Relevance
“…From their research, they suggested that SCI showed that positively and negatively worded items in these four main factors correlated each other. At the individual level, Long and Perkins(2007) reaffirmed that SOC is intimately related to social capital(neighboring, citizen participation, collective efficacy), informal(social control), communitarianism, place attachment, community confidence, and community satisfaction. He argues that place and social are inextricably bound, and studying the impact of the social alone on communityoriented construct constrains full understanding of multilevel phenomena.…”
Section: Sense Of Community (Soc) and Its Componentsmentioning
confidence: 89%
See 1 more Smart Citation
“…From their research, they suggested that SCI showed that positively and negatively worded items in these four main factors correlated each other. At the individual level, Long and Perkins(2007) reaffirmed that SOC is intimately related to social capital(neighboring, citizen participation, collective efficacy), informal(social control), communitarianism, place attachment, community confidence, and community satisfaction. He argues that place and social are inextricably bound, and studying the impact of the social alone on communityoriented construct constrains full understanding of multilevel phenomena.…”
Section: Sense Of Community (Soc) and Its Componentsmentioning
confidence: 89%
“…Moreover, highly dense neighborhoods in urban area are often associated with emotional environment that makes people's relationships superficial, instrumental, and impersonal. Several studies report that increased level of the sense of community is fostering more feelings of being real neighborhood environment which could be found in traditional villages (Long & Perkins, 2007;McMillan & George, 1986;Glynn, 1981). Further, it is known that high level of sense of community contributes to the safe, and soundness of community, thus making a better place to live.…”
Section: Introductionmentioning
confidence: 99%
“…The third type of data was social participation. The variables of social participation are 'membership of residents association' (Ohmer & Beck 2006); 'presence of vigilante groups' (Ohmer & Beck 2006;Long & Perkins 2007). 'Friendship in the neighbourhood'and,'feeling of friendliness'.…”
Section: Methodsmentioning
confidence: 99%
“…Others (Long & Perkins 2007) considered social participation as one of the four dimensions of social capital (others being collective efficacy, social cohesion and social disorganization). Indeed participation in leisure or recreation activities is regarded by many researchers as an essential component of an individual's sense of well-being resulting in positive benefits such as self-improvement and family functioning (Wood et al 2007).…”
Section: Social Participation and Sense Of Communitymentioning
confidence: 99%
See 1 more Smart Citation